A Multi Criteria Approach for Computer Purchase Among International Graduate Students - Bataineh, Mahmoud Salem Barakat (2009)
It is undisputable that possession of a personal computer (PC) is necessary for university students. It is vital to consider the attributes that make consumer decision-making easier, comfortable and therefore, leading to an appropriate PC purchase. First, the study aims to determine the ranking of attributes of a computer required by a university student, where Rank-Ordered-Centroid (ROC) method is employed. The findings indicate that the most important attribute is processor, followed by hard drive, price, memory card, warranty, size, screen resolution, Ethernet, weight and DVD. Second, the study constructs Computer Preference Index (CPI) required by a university student. The CPI is calculated by using Simple Additive Weighting (SAW) which is one of the Multi-Criteria Decision-Making (MCDM) methods. The study only focuses on four brands of PC (Toshiba, Dell, HP Compaq and Acer). The result shows that the rank of computers according to brands is the same, even though two types of weights are used. For example, for Toshiba brand, the most preferable computer is M200-E4314, for Dell, it is Inspiron I1420 [T8100], for HP Compaq, Presario V3632, and for Acer, Aspire 4920-601G25L. The CPIs for all computers based on two types of weights are different, but the most preferred computer is HP Compaq Presario V3632 and the least preferred computer Acer Aspire 4920-5AA0516MI are the same.